Robust mean variance portfolio selection model in the jump-diffusion financial market with an intractable claim. (3rd July 2017) - Wang, Ming-hui; Yue, Jia; Huang, Nan-jing
Abstract : In this paper, a continuous-time robust mean variance model in the jump-diffusion financial market with an intractable claim is considered, in which the price processes of the assets not only are driven by the Brownian motion, but also have the Poisson jumps. By combining the martingale representation theorem and the quantile formulation method, an explicit closed-form solution of the robust mean-variance portfolio selection model is given under some suitable assumptions.